Child and Youth Cooking Programs: More Than Good Nutrition?. Issue 4 (2nd October 2017) - Utter, Jennifer; Fay, Anna P.; Denny, Simon
ABSTRACT: Given the changes to the global food environment and youth eating behaviors, an interest in culinary education for young people has reemerged. This review describes the experiential cooking programs for children and young people that have been conducted and evaluated to date. Youth cooking programs appear to result in better nutrition and cooking skills. Moreover, it is suggested that cooking programs may also positively influence social aspects of youth well-being. However, evaluations of these programs have been poor, and large-scale, randomized controlled trials are needed to quantify the true impact that cooking programs can have on nutrition and social well-being.